DETERMINANT ANALYSIS OF FACTORS AFFECTING MUSTAHIK WELFARE WITH MEDIATED BUSINESS DEVELOPMENT - Meilda Avionita Anggraini; Firman Setiawan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
This study aims to analyze the impact of the application of business capital assistance, training, training, and mustahik work ethic on mustahik welfare through business development. Sampling using non probability sampling technique with purposive sampling approach. The sample of this study were 50 mustahik members of the Independent Business Community (IBC) at the Al-Falah Surabaya Social Fund foundation who met the research criteria. This study uses quantitative methods with the PLS (Partial Least Square) approach through a path analysis model. The results of this study indicate the statistical t value for the variables of training, mentoring, and Islamic work ethic, respectively 1.987, 3.341 and 4.011> t table 1.960 so that it is said to have a significant influence on the welfare of mustahik through its business development. While the statistical t value of the business capital variable 0.402 < t table 1.960 does not have a significant effect on the welfare of mustahik through business development. In conclusion, the variables of training, mentoring and Islamic work ethic have a significant effect on the welfare of mustahik mediated by business development. While the business capital variable has no significant effect on the welfare of mustahik mediated by business development.